Glass powders and reactive silicone binder: Application to digital light processing of bioactive glass-ceramic scaffolds. Issue 16 (November 2020) - Elsayed, Hamada; Picicco, Martiniano; Dasan, Arish; Kraxner, Jozef; Galusek, Dusan; Bernardo, Enrico
Abstract: Powdered 'silica-defective glasses', mixed with silicones, have been already shown as a promising solution for the sintering, in air, of glass-ceramics with complex geometries. A fundamental advantage of the approach is the fact silicones act as binders up to the firing temperature, at which they transform into silica. A specified 'target' glass-ceramic formulation is achieved through the interaction between glass powders and the binder-derived silica. The present paper is dedicated to the extension of the approach to the digital light processing of reticulated glass-ceramic scaffolds, for tissue engineering applications, starting from glass powders suspended in an engineered photocurable silicone-based binder. The silicone component, besides providing an extended binding action up to the maximum firing temperature, stabilizes the 3D-printed shapes during sintering. The formation of a rigid silica skeleton, from the transformation of the silicone binder, prevents from excessive viscous flow of softened glass. The final phase assemblage does not depend simply on glass devitrification but also on the glass/silica skeleton interaction.